Sediment Exchange Between the Created Saltmarshes of Living Shorelines and Adjacent Submersed Aquatic Vegetation in the Chesapeake Bay - Vona, Iacopo; Palinkas, Cindy M.; Nardin, William (Frontiers in Marine Science, 2021)
Rising sea levels and the increased frequency of extreme events put coastal communities at serious risk. In response, shoreline armoring for stabilization has been widespread. However, this solution does not take the ecological aspects of the coasts into account. The “living shoreline” technique includes coastal ecology by incorporating natural habitat features, such as saltmarshes, into shoreline stabilization. However, the impacts of living shorelines on adjacent benthic communities, such as submersed aquatic vegetation (SAV), are not yet clear. In particular, while both marshes and SAV trap the sediment necessary for their resilience to environmental change, the synergies between the communities are not well-understood. To help quantify the ecological and protective (shoreline stabilization) aspects of living shorelines, we presented modeling results using the Delft3D-SWAN system on sediment transport between the created saltmarshes of the living shorelines and adjacent SAV in a subestuary of Chesapeake Bay. We used a double numerical approach to primarily validate deposition measurements made in the field and to further quantify the sediment balance between the two vegetation communities using an idealized model. This model used the same numerical domain with different wave heights, periods, and basin slopes and includes the presence of rip-rap, which is often used together with marsh plantings in living shorelines, to look at the influences of artificial structures on the sediment exchange between the plant communities. The results of this study indicated lower shear stress, lower erosion rates, and higher deposition rates within the SAV bed compared with the scenario with the marsh only, which helped stabilize bottom sediments by making the sediment balance positive in case of moderate wave climate (deposition within the two vegetations higher than the sediment loss). The presence of rip-rap resulted in a positive sediment balance, especially in the case of extreme events, where sediment balance was magnified. Overall, this study concluded that SAV helps stabilize bed level and shoreline, and rip-rap works better with extreme conditions, demonstrating how the right combination of natural and built solutions can work well in terms of ecology and coastal protection.